Strength Analysis Plastic Deformed Centrifugal Pumps - Edi Saputra; Nuzuli Fitriadi (Jurnal Inotera, 2021)
The G-3503 centrifugal pump functions to flow Diethanolamine fluid with a viscosity of 380 Cp which functions to reduce H2S and CO2 levels in natural gas. When operating, the pump shaft experiences a torque load which causes the shaft to be twisted by 80. From the exact and finite element analysis results, the shear stress that occurs on the shaft is greater than the shear stress of the shaft material. Thus, the shaft is deformed plastically. The shear stress that occurs is 164 MPa